Recurrence quantification analysis of body response to functional electrical stimulation on hemiplegic subjects - Acharya, U. Rajendra (2013)
Hemiplegia means paralysis of half of the body. It commonly occurs following "stroke", which is due to impedance of blood supply to the brain, hence also termed as "cerebrovascular accident" (CVA). As a consequence of this, the brain tissues suffer from ischemic damage resulting in several symptoms, such as mere weakness, numbness to complete loss of power (paralysis). In order to restore or improve the lost functional movement of the body of the stroke-affected and hemiplegic subjects, a method called functional electrical stimulation (FES) has often been employed as the measure of rehabilitation. FES makes use of low levels of electrical current to activate the nerves and then the muscles, affected. The response of the body to this electrically triggered nervous stimulation could be recorded through different bio-signals. In our work, we measured the accelerometers of hemiplegic patient in two states; with FES and without FES. The nonlinear and nonstationary walking-function-related accelerometers are analyzed using recurrence plots (RP), which helps to visualize the dynamic behavior of the signals. The RPs of electromyography (EMG) signals with stimulation showed distinct periodicity and rhythm when compared to that without stimulation. In addition, we extracted recurrence quantification analysis (RQA) parameters from RP to quantify the obtained information from the RP. Lower values were observed for most of the RQA parameters with FES than obtained without FES. This also confirmed the fact that FES is very useful in bringing more order, rhythm and better control in the physical activities of hemiplegic people.